Analisis Pengendalian Persediaan Bahan Baku dalam Upaya Menekan Biaya Produksi pada Mie Ayam Pahlawan di Tarakan - Hidayat, Nurul; Risal; Ramadhan, Dwi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to assess the effectiveness of inventory control applied by Mie Ayam Pahlawan in optimizing production costs and determining the economically optimal order quantity for raw materials, as well as minimizing the total inventory cost. The study employs a quantitative descriptive method, focusing on the company within a specific timeframe, gathering data and information relevant to the research objectives. Descriptive analysis techniques are utilized to analyze data related to raw material inventory control issues in efforts to reduce production costs, using the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) methods. The findings indicate that the company can achieve cost savings by adopting the POQ method, where ordering costs are lower compared to the EOQ method or the current method employed by the company. The frequency of raw material purchases using the company's method is higher than the POQ method (Period Order Quantity).